Nerve ultrasound normal values – Readjustment of the ultrasound pattern sum score UPSS - Grimm, Alexander; Axer, Hubertus; Heiling, Bianka; Winter, Natalie (Clinical neurophysiology, 2018)
•Normal values and upper limits are necessary for ultrasound studies.•Age-, gender, height- and weight-dependency was not consistently found.•Age and gender dependency were most pronounced in the larger tibial nerves of elderly men. Reference values are crucial for nerve ultrasound. Here, we reevaluated normal nerve and fascicle cross-sectional area (CSA) values in humans and compared them to published values. Based on these data, ultrasound pattern sum score (UPSS) boundary values were revisited and readjusted. Ultrasound of different peripheral nerves was performed in 100 healthy subjects at anatomically defined landmarks. Correlations with age, gender, height and weight were calculated. Overall, correspondence to other published reference values was high. Gender-dependency was found for the proximal median nerve. Dependency from height occurred in the tibial nerve (TN). Weight-dependency was not found. However, the most obvious differences were found in the TN between men >60 years and women <60 years. Thus, general boundary values were defined using the mean plus the twofold standard deviation for all subjects and nerve segments except for the TN, in which different cut-offs were proposed for elder men. Accordingly, the cut-offs for the UPSS were re-adjusted, none of the individuals revealed more than 2 points at maximum. The influence of distinct epidemiological factors on nerve size is most prominent in the TN, for which thus several normal values are useful. Adjusted reference values improve the accuracy of the UPSS.